Exploring Entrepreneurial Orientation’s Impact on Innovation and Academic Performance in Malang City’s Consumer Cooperatives - Rofiaty, Rofiaty; Rahmat, Ainur Rifqi Almahdani; Nisa, Khoirun; Nurcholifah, Siti (Jurnal Ilmiah Manajemen & Bisnis, 2023)
The objects studied and the areas studied in this research are how a business can maintain sustainability and increase its business competitiveness, in this case, cooperatives in the city of Malang, as well as to grow the community's economy through the implementation of entrepreneurship-oriented strategies, the business environment towards innovation and performance strategies cooperative. The role of cooperatives in creating jobs and improving the welfare of their members with the principle that cooperatives are run "from, by, and for their members." The business world, primarily cooperatives, and small and medium enterprises, faces various challenges and must achieve Performance that will increase competitiveness and maintain business sustainability. For this reason, cooperatives must be more creative, innovative, agile, and intelligent in implementing their strategies. This research examines and analyzes the relationship between the business environment, entrepreneurial orientation, innovation, and Performance. Business in the era of information technology requires organizations to adapt to environmental changes and business competition, which is increasingly stringent, requiring cooperatives to provide products and services that are more market-oriented in order to be able to produce innovations that are in line with technological advances and market segments, so that Performance will increase.